2017
DOI: 10.1002/jctb.5410
|View full text |Cite
|
Sign up to set email alerts
|

Protein adsorption in anion exchange resins – effects of polymer grafting, support structure porosity, and protein size

Abstract: BACKGROUND: Anion exchange resins are used extensively for the purification of acidic proteins. Grafting charged polymers to a rigid porous structure has been shown to improve performance under varying conditions. Understanding the underlying mechanisms is important for the optimum design and selection of material properties and operating conditions. RESULTS: Positively charged grafted polymers incorporated into a rigid, porous polymeric backbone structure are found to significantly enhance adsorption capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…R esistance t o i ntraparticle d iffusion is usually an important limiting step in the control of uptake kinetics (in addition to resistance to film d iffusion, pr edominant du ring th e first minutes of contact, bulk diffusion, and the proper reaction rate). Using small particle sizes obviously limits the effect o f r esistance t o intraparticle diffusion; this effect can be even minored when the sorbent is highly porous (high specific surface area, pore size, pore volume, etc) [64][65][66]. The textural properties (analyzed by BET method) showed that the specific surface area was relatively small (i.e., 16 m 2 g −1 ).…”
Section: Sorption Studies 321 Effect Of Ph and Interpretation Of Smentioning
confidence: 99%
“…R esistance t o i ntraparticle d iffusion is usually an important limiting step in the control of uptake kinetics (in addition to resistance to film d iffusion, pr edominant du ring th e first minutes of contact, bulk diffusion, and the proper reaction rate). Using small particle sizes obviously limits the effect o f r esistance t o intraparticle diffusion; this effect can be even minored when the sorbent is highly porous (high specific surface area, pore size, pore volume, etc) [64][65][66]. The textural properties (analyzed by BET method) showed that the specific surface area was relatively small (i.e., 16 m 2 g −1 ).…”
Section: Sorption Studies 321 Effect Of Ph and Interpretation Of Smentioning
confidence: 99%
“…In line with the stoichiometric displacement model, the anions compete with proteins for binding sites on the positively charged ligand, and the more negatively charged anions are harder to displace, which ultimately results in a lower DBC 10. 23 …”
Section: Resultsmentioning
confidence: 99%
“…Nuvia HP-Q and Nuvia aPrime 4A (henceforth referred to as Nuvia aPrime) were obtained from Bio-Rad Laboratories (Hercules, CA, USA), while Capto Adhere ImpRes (henceforth referred to as Capto Adhere) was obtained from Cytiva (Marlborough, MA, USA). Relevant physical properties of these resins have been reported previously 18,19 and are summarized in Table 1. Nuvia HP-Q is the same as the prototype identified as BRX-Q4 in Zhu et al, 19 while Nuvia aPrime 4A is the same as the prototype identified as Nuvia aPrime 1 in Roberts et al 18 Both Nuvia resins are based on a hydrophilic synthetic polymeric matrix with a bimodal pore distribution consisting of large pores (>100 nm radius) and small pores (<20 nm radius).…”
Section: Experimental Materialsmentioning
confidence: 99%